A Methodology for Cutting Force Prediction in Side Milling - BAKIR, BARKIN; KURT, MUSTAFA (TAYLOR & FRANCIS INC, 2014)
This article describes a methodology based on force distributions for predicting cutting forces in side milling 7075-T651 aluminum. The methodology includes a practical mechanism for gathering experimental data. Milling forces on each disc are measured by experimentally dividing the cutter into discs for determining the milling coefficients. Force distributions are characterized as functions of cutting and edge forces, including cutter geometry and cutting parameter effects. In contrast to previous researches, the coefficients are determined considering relations between load and shear. Owing to its high performance, this methodology can be effectively used to improve machining accuracy in side milling.
Keywords: Design; Tooling; Simulation; Forces; Processes; Parameters; Milling; Aluminum; SURFACE-ROUGHNESS; END; COEFFICIENTS; MODEL; OPTIMIZATION; SIMULATION